Efecto citotóxico del extracto acuoso de las hojas de Annona cherimola en una línea celular de cáncer de pulmón humano en un medio de cultivo con pH neutro - Garrochamba Peñafie, Kleber Gabriel (2015)
The lungs are often affected by diseases such as lung cancer, a situation in which cells change their characteristics and transform into malignant due to the inhalation of smoke snuff, head at least 80% (American Cancer Society, 2014) . This research aims to: verify the cytotoxic activity of neutral pH aqueous extract of leaves of Annona cherimola front lines of lung cancer in the Province of Loja. The study applied a prospective model of Experimental-kind in the center of Biotechnology of the National University of Loja, employing methods and techniques for determining cell viability and proliferation, the first by counting viable and dead cells in Neubauer chamber and coloring trypan blue, and the second through the viable cell count subsequent to incubation media at different times. By tests made between the aqueous extract and cisplatin increased level of cytotoxic effect against cisplatin equivalent to 84.1% cell lung cancer line (A549) it was determined. Well as proliferation or cell confluence was given by the culture medium over the A549 cell line equivalent to 78.3% relative to the aqueous extract equal to 74% at 36 hours of incubation. Keywords: acetogenina, cytotoxicity, cisplatin